PENGEMBANGAN TES DIAGNOSTIK THREE TIER TEST PADA MATERI SUHU DAN KALOR UNTUK SMP - Sutiana, Sutiana; Maria Silitonga, Haratua Tiur; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to develop a three tier diagnostic test of temperature and heat subject in junior high school. This research explained the characteristics of diagnostic test. The method in this research was developed from Borg and Gall development model which has been simplified.The test consists of 30 multiple choice questions with reason and level of confidence. The test involved 31 students on small-scale trials, and 92 students on large-scale trials. The developing diagnostic test can be used to reveal the misconceptions of students, with the characteristics of 1) high validity level, 2) high reliability, 3) low difficulty level, 4) problems made with simple language 5) designed to detect common mistakes, 6) developed based on early conceptions of students. Based on the characteristics, a question that can be used as many as 13 questions from 30 questions developed. Keywords: development of three tier diagnostic test, test characteristics, temperature and heat